Interplay between innate-like T-cells and microRNAs in cancer immunity - Mohammad Javad Yousefi; Yashmin Afshar; Amirmohammad Amoozadehsamakoosh; Alma Naseri; Fereshteh Soltani; Niloufar Yazdanpanah; Kiarash Saleki; Nima Rezaei (Discover Oncology)
Abstract Innate-like T cells (ILTCs) have recently emerged as a new target of several cancer immunotherapies. Some unique features, such as rapid MHC-independent recognition of antigens, performing heterogeneous anti-tumor activities, and being less susceptible to tumor-induced suppression, suggest promising roles of ILTCs in cancer immunology. On the other hand, these cells exhibit a dualistic nature in cancer, which includes both pro-tumor and anti-tumor effects, highlighting the importance of the complex regulatory environment of their functioning and activation. The functions and evolution of ILTC are greatly influenced by microRNAs (miRNAs), small non-coding RNA molecules that mediate post-transcriptional regulation. Considering the kind of ILTCs, miRNA, and cancer type, this interaction resembles both a tumor promoter and suppressor. ILTC functions and evolution are closely associated with microRNAs (miRNAs), small noncoding RNA molecules that play posttranscriptional regulatory roles. Depending on the type of ILTCs, miRNA, and cancer, this interaction resembles both a Tumor promoter and a tumor Suppressor. This review addresses the complicated relationship between ILTCs and different miRNAs, such as miR-155, let-7 s, and miR-181a, expressed in tumor cells, ILTCs, or packed in tumor-derived exosomes. We will underscore the synergetic effects of the expression of miRNA in tumor and immune cells, influencing ILTC’s function and cancer progression. We emphasized the recent and innovative therapeutic approaches, novel delivery systems, and CAR-T cell-based strategy, and the therapeutic potential of modifying the expression of miRNA to regulate the miRNA expression to modulate ILTC activity and improve cancer treatment.